2016
DOI: 10.1007/s00226-016-0878-1
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation of acoustic tomography images for the measurement of wood decay

Abstract: In the assessment of standing trees, an acoustic tomographic device is a valuable tool as it permits to acquire data from the inner part of the trees without causing them to fall down unnecessarily. The interpretation of the images produced by these devices is part of the diagnosis process for urban trees management. This paper presents a segmentation methodology to identify defective regions in cross-section tomographic images obtained with an Arbotom® device. Two trunk samples obtained from a Blackwood Acaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This is a well-established tool for the assessment of a tree's structural soundness, with numerous studies over the past 20 years testing its application under various conditions. Many research teams have confirmed the effectiveness of acoustic tomography in detecting tree decay [43][44][45][46][47][48][49][50]. At the beginning of the 21st century, research was conducted on the health condition of urban trees using various research methods (electrical and acoustic tomography and GPR), achieving various degrees of success with them.…”
Section: Discussion-tomograph As a Tool Supporting The Management Of Historical Greenerymentioning
confidence: 99%
“…This is a well-established tool for the assessment of a tree's structural soundness, with numerous studies over the past 20 years testing its application under various conditions. Many research teams have confirmed the effectiveness of acoustic tomography in detecting tree decay [43][44][45][46][47][48][49][50]. At the beginning of the 21st century, research was conducted on the health condition of urban trees using various research methods (electrical and acoustic tomography and GPR), achieving various degrees of success with them.…”
Section: Discussion-tomograph As a Tool Supporting The Management Of Historical Greenerymentioning
confidence: 99%
“…The images for the defective cases were segmented using a threshold. It has been previously shown that using a threshold value to separate healthy and defective regions is not always the most suitable way of interpreting tomograms (Espinosa et al 2017). In this specific case, the thresholding segmentation was chosen because it allowed comparing quantitatively the two image reconstruction methods.…”
Section: Assessment Of Decay Detectionmentioning
confidence: 99%
“…In addition to identification of decay, Alves et al (2015) showed the importance of AT in determining elastic constants of Muiracatiara Brazilian wood (Astronium lecointei). Recently, different image reconstruction methods have been developed and presented (Espinosa et al 2017;Du et al 2018). According to the reliable representation of cavities and degraded wood, AT can be used to predict the loss of load-bearing capacity for trees with internal defects (Burcham et al 2019).…”
Section: Introductionmentioning
confidence: 99%